IMPACTS OF ECONOMIC ACTIVITIES TO THE WATER QUALITY OF HIEU RIVER IN CHAU HANH COMMUNE, QUY CHAU DISTRICT, NGHE AN PROVINCE - Quang Bao, Tran; Thanh Quang, Tran (Journal of Forestry Science and Technology, 2017)
It has been widely accepted that there is a close relationship between the economic activities and water quality. This study aims to analyze the influence of economic activities, especially the various land use types on the water quality of Hieu river in Chau Hanh - a commune in mountainous areas of Vietnam based on the water quality indicator data with the characteristics of riparian buffer. The results indicated that there was significant correlation between land use in the riparian buffer and the water pollution. The loss of plant cover is proportional to the increase in the level of water pollution. The results can provide scientific reference for the local land use optimization and water pollution control.